ANALISIS JARINGAN WIRELESS LOCAL AREA NETWORK (WLAN) DI GEDUNG TEKNIK ELEKTRO UNIVERSITAS JENDERAL ACHMAD YANI UNTUK LAYANAN VIDEO LIVE STREAMING YOUTUBE - M. Reza Hidayat; Thio Fajar Shantony (Jurnal Elektro dan Telekomunikasi Terapan (e-Journal), 2021)
During this COVID-19 pandemic, internet users are increasing. Most of the activities are done online to avoid the spread of the virus. The YouTube platform is an internet facility that provides various kinds of information through video, both video streaming and live streaming. The rapid development of technology, especially in electronic devices that provide wireless devices, makes it easier for users to access the internet in various places that provide internet access. Youtube live streaming users via wireless networks are different from wired networks because the characteristics of the network are limited and the characteristics of live streaming using wireless require different handling. As a first step to get optimal internet service, it is necessary to measure the average value of internet network service performance using the quality of service parameter when accessing YouTube live streaming video services on a wireless local area network in the Electrical Engineering building of Jenderal Achmad Yani University. This research was conducted using two methods, namely changes in frame rate and resolution as well as changes in the direction and distance of the user from the access point by utilizing the Perpus_FT Unjani hotspot and TPL-TE-Unjani SoB2 hotspot. The analyzed quality of service parameters consist of delay, jitter, packet loss, and throughput. The results of the analysis using the quality of service parameters for YouTube live streaming videos in the research method of changing frame rates and resolutions produce a satisfactory average index value at the Perpus_FT Unjani hotspot of all resolutions used with a frame rate of 30 fps getting an average index value of 3.5 and a frame rate of 60 fps gets an average index value of 3.25. At the TPL-TE-Unjani hotspot, SoB2 produces a satisfactory average index value of all the resolutions used with a frame rate of 30 fps and 60 fps gets an average index value of 3.5. While the results of the analysis using the quality of service parameters for YouTube live streaming videos on the research method of changes in direction and the user's distance from the access point produces a satisfactory average index at a maximum distance of 5 meters in each direction. In the Unjani Library_FT hotspot with north, south, west directions, the average index value is 3.75 and the east is 3.5. Meanwhile, in the TPL-TE-Unjani SoB2 hotspot, the north and east directions produce an average index value of 3.75, while the south and west directions produce an average index value of 3.5 and 4. Both methods are assessed based on the TIPHON standard.